2020
DOI: 10.7243/2055-2386-7-8
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year Evaluation of the NFL Combine. Do Combine Results Correlate with Career Longevity for NFL Offensive players?

Abstract: Background:The National Football League (NFL) combine has been found to play a significant role in NFL draft decisions. Previous studies have demonstrated correlations between a player's combine metrics and draft position and performance, but no study has investigated the purposes of our study, the relationship between these combine tests and NFL career longevity. Methods: A retrospective review of combine test results from all offensive players participating in the NFL combine from 2005-2015 was completed. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Published online: 2021-08-10 reer longevity and how a player's draft status may be negatively affected [4][5][6][7][8].…”
Section: E59mentioning
confidence: 99%
See 2 more Smart Citations
“…Published online: 2021-08-10 reer longevity and how a player's draft status may be negatively affected [4][5][6][7][8].…”
Section: E59mentioning
confidence: 99%
“…For example, a study examining the combine from 1987 to 2000 showed players receiving a high orthopedic grade having a mean career length of 42 games, players with a low orthopedic grade playing 34 games, and players with a failed orthopedic grade playing 19 games 4 . Other studies have shown how injury prior to the combine, among other characteristics, can help estimate career longevity and how a player’s draft status may be negatively affected 4 5 6 7 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 , 42 , 46 The Lisfranc ligaments are composed of dorsal, plantar, and interosseous components in order of increasing strength based on previous biomechanical models. 4 , 15 , 35 , 46 …”
mentioning
confidence: 99%
“… 41 , 46 These ligamentous ruptures may present subtly without subluxation, dislocation, or fracture but will include pain, swelling, and tenderness over the area and are often misdiagnosed as a “foot sprain.” If left untreated, the ligamentous injury can lead to increased pain, instability, osteoarthritis, and morbidity. 4 , 18 , 46 Furthermore, younger patients and athletes, eager to return to physical activity, may have prolonged periods of disability even with less severe ligamentous injuries. 11 …”
mentioning
confidence: 99%